Content and specificity of the Anti-SARS-CoV-2 antibodies in solutions for immunoglobulin replacement therapy - Milota, Tomas; Smetanova, Jitka; Zelena, Hana; Rataj, Michal; Lastovicka, Jan; Bartunkova, Jirina (International immunopharmacology, 2023)
BACKGROUND: Specific antibodies are important for post-vaccination and post-infection immune responses against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The role of antibodies in preventing and treating Coronavirus disease 2019 (COVID-19) in high-risk populations has been highlighted through the use of virus-specific monoclonal antibodies, which has raised the question of immunoglobulin replacement therapy (IRT) used in immunocompromised patients. METHODS: Virus-specific anti-receptor-binding domain (RBD) and anti-nucleocapsid protein (NCAP) antibodies (assessed using a chemiluminescence assay and virus-neutralizing antibodies (virus neutralization test against Delta and Omicron variants)) were analyzed in 20 batches of 10 % (100 mg/mL) immunoglobulin solutions for intravenous IRT from two commercially available producers between January 2022 and March 2023 for clinical use. RESULTS: Anti-RBD and anti-NCAP antibodies were detected in all 20 batches of assessed IRT solutions (mean concentrations of 2817 IU/mL and 2380 IU/mL, respectively). Notably, the concentration of the virus-specific antibodies increased continuously during the follow-up period (from 822.5 IU/mL to 4066.4 IU/mL and 102 IU/mL to 3455.9 IU/mL). These antibodies demonstrated high virus-neutralizing activity against the Delta variant (mean titers of 436 and 325) but were limited to the Omicron variant (mean titers 78 and 70). The differences observed between the two brands were not statistically significant. CONCLUSION: IRT solutions contain high concentrations of anti-SARS-CoV-2 specific antibodies, which may prevent COVID-19; however, the efficacy can be influenced by variable virus-neutralizing activities against different viral strains. Therefore, appropriate IRT should be combined with other approaches, such as vaccination or pre- and post-exposure prophylaxis. Passively transmitted specific antibodies may also lead to false-positive serological test results.
Keywords: Humans; Antibodies, Neutralizing; Immunization, Passive; nukleokapsida - proteiny; Receptors, Virus; virové receptory; neutralizující protilátky; Delta variant; lidé; Omicron variant; Nucleocapsid Proteins; Nucleocapsid protein; COVID-19; Receptor-binding Domain; Immunoglobulin replacement therapy; SARS-COV-2; protilátky virové; Antibodies, Viral; SARS-CoV-2; pasivní imunizace